Persebaran Diatom Epipelik secara Vertikal pada Ekosistem Mangrove Muara Sungai Banjir Kanal Timur Semarang - Hariyati, Riche; Suprobowati, Tri Retnaningsih; Chotidjah, Siti (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2009)
Diatom is a widespread and cosmopolite micro alga, some can used as bio-indicator of the past environmental change because of its sensivity to its habitat condition and because it is wellfossilized. This study has been done on the estuary of Banjir Kanal Timur Semarang which has ecosystem mangrove; this region is often affected by coast abrasion, flooded by spring-tideinundation water, rain, and freshwater inflow of the river. The study was aimed to examine relative abundance difference, diversity, and vertically variety level of diatom per 2 cm per sediment layer. Sampling method used in the research was â€œJudgemental Random Samplingâ€. The result shows that diatom in the mangrove ecosystem of Banjir Kanal Timur Estuary is stable in the upper layer sediment and midle from lower layer and the mangrove ecosystem of Banjir Kanal Timur Estuary is affected by freshwater estuary, based on the domination of the existence of freshwater diatoms (Navicula radiosa, Synedra ulna, Meridion circulare, Sellaphora bacillum, and Eunotia lunula) onthe 8-20 layer.